RANCANG BANGUN APLIKASI SMART (SISTEM PENGADUAN KERUSAKAN BARANG TERINTEGRASI) - Ifanka, Rista; Muhammad Vikri Bagas Maulana; Alvian Ramandika; Umi Chotijah (JOURNAL SAINS STUDENT RESEARCH, 2025)
Manual procedures for reporting damaged assets in institutions often lead to delayed handling, unclear tracking, and inconsistent documentation. To address these problems, a web-based system called SMART (Integrated Goods Damage Reporting System) was developed to digitize and simplify the reporting workflow for better efficiency. The system was developed using the Waterfall model, following sequential steps including requirement identification, system planning, implementation, testing, and maintenance to maintain reliable and stable operation. The application was developed using PHP for coding implementation and MySQL for managing its database, integrated with a user interface built through the AdminLTE framework on a protected intranet network. Black-box testing verified that each system component performed according to its design and met user needs for precision, responsiveness, and usability. Overall, the SMART system enhances efficiency, data integrity, and transparency in the process of managing institutional asset maintenance.